Expresiones lingüísticas en la plataforma tiktok: Identidad y pertenencia en adolescentes y jóvenes del Ecuador - Oña Lalvay, Dayana Maricela (2025)
This research focuses on analyzing the linguistic expressions used on the TikTok platform and how these significantly influence the construction of identity, generating a sense of belonging in adolescents and young people in Ecuador. Through a qualitative and descriptive approach, it is understood how language affects the process of identity construction. The study shows the role of TikTok in the creation of new forms of language based on the observation carried out both on the TikTok platform and in the focus groups where it is possible to identify dynamics in the use and recognition of linguistic expressions as well as in the mode of use and impact it has within social dynamics.